Dari Pentakosta Ke Ruang Kelas: Membangkitkan Spiritualitas Misi dalam Pendidikan Kristen - Talizaro Tafonao; Moralman Gulo; Rita evimalinda; Emmiria Hutabarat; Agiana Her Vinshu Ditakrist (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
Christian education faces significant challenges in integrating the values of missional spirituality into its curriculum and teaching practices, particularly in the context of globalization, secularization, and a declining awareness of spiritual calling among educators. This study aims to examine the extent to which Pentecostal theological values such as prayer, worship, and mission are implemented in Christian education and how these values contribute to the formation of students' character and spirituality. Employing a descriptive qualitative method, data were collected through in-depth interviews, classroom observations, curriculum document analysis, and open-ended questionnaires administered to teachers and students. The findings reveal that the integration of missional spirituality remains partial and lacks structured incorporation into both curriculum and pedagogy. However, when implemented contextually, these values have been shown to enhance learning motivation, shape Christian character, and deepen students’ spiritual lives. The study concludes that Pentecostal-based missional spirituality can holistically enrich Christian education. The primary contribution of this research is the development of a conceptual model for the contextual and practical integration of missional spirituality in Christian education, aiming to bridge the gap between theoretical understanding and practical spiritual formation.